A computational fluid dynamics analysis of single and three nozzles minimum quantity lubricant flow for milling - Najiha, M. S.; M. M., Rahman (Universiti Malaysia Pahang, 2014)
A 3-dimensional computational fluid dynamics analysis of minimum quantity lubricant flow for a four-tooth milling cutter operation with single and three nozzles is presented in this paper. CFD modelling is utilized to simulate the flow distribution around a four- tooth milling. The domain of a rotating cutter along with the spraying nozzle was defined. Operating cutting and boundary conditions were defined based on previous literature. A steady-state, pressure-based, planar analysis was performed with a viscous, realizable k-ε model. A 3-D transient-case, incompressible analysis for the minimum quantity lubricant is also performed. The domain of the milling cutter is rotated at a very high spindle speed, and a single nozzle is used to investigate the effects of MQL spray. A mixture of oils and air is sprayed onto the tool. Another analysis is performed with three nozzles placed at equal angles to each other around the periphery of the tool. A 2-dimensional steady-state analysis is also carried out using CFD. The obtained results verify that the single nozzle cannot fully lubricate the rotating tool. It was observed that flow penetration into the cutting zone is dependent on the flow velocity and the number of nozzles. Hence, it can be concluded that the MQL nozzle arrangement can be improved with three nozzles with a constant mass flow rate.